Hegemony and power in the central highlands: Ranrapata, a vision from the Late Intermediate to the early colonial period - Sulca Huarcaya, Nils Ramiro (2022)
Ranrapata located in the bowels of the district of Acoria, department of Huancavelica, keeps a long occupation that goes from the Late Intermediate with the presence of the Astos, who would succumb to the arrival of the Incas. With the Spanish presence in this area, various societies would undergo structural changes in terms of their social and ideological system. The evidence identified in the archaeological excavations gives us clear indications of power hegemonies imposed at different times in a part of the peruvian central highlands.